2011
DOI: 10.1128/jcm.00287-11
|View full text |Cite
|
Sign up to set email alerts
|

Using Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry To Detect Carbapenem Resistance within 1 to 2.5 Hours

Abstract: In recent years, the percentage of carbapenem-resistant bacteria has increased at an alarming pace and become a major threat for patient survival. Carbapenemase-induced carbapenem resistance can be confirmed through the detection of carbapenem degradation using matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). This method works for strains carrying NDM-1, VIM-1, VIM-2, KPC-2, and different IMP enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
204
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(219 citation statements)
references
References 15 publications
5
204
0
10
Order By: Relevance
“…Recently, the carbapenemase activity of Gram-negative bacilli has been detected by matrix-assisted laser desorption ionizationtime of flight (MALDI-TOF) MS (Burckhardt & Zimmermann, 2011;Carvalhaes et al, 2013). This method relies on the modification of the mass spectrum profile of the carbapenem molecule by carbapenemases (Burckhardt & Zimmermann, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the carbapenemase activity of Gram-negative bacilli has been detected by matrix-assisted laser desorption ionizationtime of flight (MALDI-TOF) MS (Burckhardt & Zimmermann, 2011;Carvalhaes et al, 2013). This method relies on the modification of the mass spectrum profile of the carbapenem molecule by carbapenemases (Burckhardt & Zimmermann, 2011).…”
mentioning
confidence: 99%
“…This method relies on the modification of the mass spectrum profile of the carbapenem molecule by carbapenemases (Burckhardt & Zimmermann, 2011). Most studies have evaluated ertapenem hydrolysis by testing the Microflex LT instrument (Bruker Daltonics) (Carvalhaes et al, 2013).…”
mentioning
confidence: 99%
“…; therefore, determining the overall level of protein expression and function is becoming increasingly important in addition to sequence analysis. A few studies (Burckhardt and Zimmermann, 2011;Hrabak et al, 2011) also identified NDM-1, VIM-1, VIM-2, KPC-2, and various types of imipenem enzymes from carbapenem-resistant P. aeruginosa, K. pneumoniae, and E. coli strains by matrix-assisted laser desorption time-of-flight MS within only 1-2.5 h, with a detection sensitivity of 96.67% and specificity of 97.87%. In the present study, the carbapenemase OXA23 was very accurately identified by MS, and was consistent with the results of phenotype and genotype tests.…”
Section: Discussionmentioning
confidence: 99%
“…Basically, the MS follows the enzymatic hydrolysis of the antimicrobial agent. The sensitivity and specificity of this approach is high (97 % and 98 % , respectively) [21] and the results are available in < 3 h [95] . However, this approach must be validated in routine laboratories to consider replacing the conventional techniques (such as cefoxitin disks, or PCR to detect the mecA gene).…”
Section: Detection Of Resistancementioning
confidence: 99%
“…Recently some resistance markers to one or more antimicrobial agents have been detected by MALDI-TOF MS. Reports suggest that MS has the ability to differentiate methicillin-susceptible S. aureus from methicillinresistant S. aureus (MRSA) strains [93,94] , and also detect carbapenem resistance activity based on the detection of degradation of β -lactam antimicrobials [20,21,95] . Basically, the MS follows the enzymatic hydrolysis of the antimicrobial agent.…”
Section: Detection Of Resistancementioning
confidence: 99%